Effects of VR instructional approaches and textual cues on performance, cognitive load, and learning experience - Zhang, Hui; Zhang, Yi; Xu, Tao; Zhou, Yun (Educational technology research and development, 2024)
Virtual Reality (VR) is increasingly recognized as a promising tool to enhance learning, yet research on the use of VR instructional approaches for online learning remains limited. The present study aims to address this research gap by examining the effects of VR instructional approaches and textual cues on learning. We conducted an educational VR study using a 2 × 2 + 1 between-subjects design involving 67 secondary vocational students. Participants learned computer assembly online and were exposed to either vicarious experience or direct manipulation instructional approaches, with or without textual cues. A control group received traditional online instruction using slides. We collected retention, transfer learning outcomes, cognitive load, and learning experience of students. The findings indicated that while vicarious VR had no effects on long-term retention, transfer, and learning experience, there were significant positive effects on the immediate acquisition of knowledge. Textual cues did not affect learning in general. However, for immediate knowledge gain, they did provide a positive boost to learning in VR involving direct manipulation, while they were unnecessary in vicarious VR experiences. This study contributes to how the cueing principle can be extended to educational VR contexts and expands the knowledge of vicarious VR learning.